International Joint Ventures and Internal vs. External Technology Transfer: Evidence from China - Kun Jiang; Wolfgang Keller; Larry D. Qiu; William Ridley (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper studies international joint ventures, where foreign direct investment is performed by a foreign and a domestic firm that together set up a new firm, the joint venture. Employing administrative data on all international joint ventures in China from 1998 to 2007—roughly a quarter of all international joint ventures in the world—we find, first, that Chinese firms chosen to be partners of foreign investors tend to be larger, more productive, and more likely subsidized than other Chinese firms. Second, there is substantial international technology transfer not only to the joint venture itself but also to the Chinese joint venture partner firm. Third, with technology spillovers typically outweighing negative competition effects, joint ventures generate net positive externalities to other Chinese firms in the same industry. Joint venture externalities are large, perhaps twice the size of wholly-owned FDI spillovers, and it is R&D-intensive firms, including the joint ventures themselves, that benefit most from these externalities. Furthermore, the positive external joint venture effect is larger if the foreign firm is from the U.S. rather than from Japan or Hong Kong, Macau, and Taiwan, while this effect is virtually absent in broad sectors that include economic activities for which China's FDI policy has prohibited joint ventures.
Keywords: F14; F23; O34; 330; international joint ventures; partner selection; technology spillovers; foreign direct investment; competition effects